Commercial Biocides Induce Transfer of Prophage Φ13 from Human Strains of Staphylococcus aureus to Livestock CC398 - Tang, Yuanyue; Nielsen, Lene N.; Hvitved, Annemette; Haaber, Jakob K.; Wirtz, Christiane; Andersen, Paal S.; Larsen, Jesper; Wolz, Christiane; Ingmer, Hanne (Frontiers in Microbiology, 2017)
Human strains of Staphylococcus aureus commonly carry the bacteriophage ΦSa3 that encodes immune evasion factors. Recently, this prophage has been found in livestock-associated, methicillin resistant S. aureus (MRSA) CC398 strains where it may promote human colonization. Here, we have addressed if exposure to biocidal products induces phage transfer, and find that during co-culture, Φ13 from strain 8325, belonging to ΦSa3 group, is induced and transferred from a human strain to LA-MRSA CC398 when exposed to sub-lethal concentrations of commercial biocides containing hydrogen peroxide. Integration of ΦSa3 in LA-MRSA CC398 occurs at multiple positions and the integration site influences the stability of the prophage. We did not observe integration in hlb encoding β-hemolysin that contains the preferred ΦSa3 attachment site in human strains, and we demonstrate that this is due to allelic variation in CC398 strains that disrupts the phage attachment site, but not the expression of β-hemolysin. Our results show that hydrogen peroxide present in biocidal products stimulate transfer of ΦSa3 from human to LA-MRSA CC398 strains and that in these strains prophage stability depends on the integration site. Knowledge of ΦSa3 transfer and stability between human and livestock strains may lead to new intervention measures directed at reducing human infection by LA-MRSA strains.